Propuesta para el uso exclusivo de la tasa interna de retorno modificada en la toma de decisión de proyectos industriales de inversión - Medina, J.R.; Romero, R.L; Pérez, G.A. (Nexo Revista Científica, 2013)
Internal Rate of Return (IRR) is the method of assessing profitability of investment projects better known. It represents, in the traditional interpretation, the interest rate earned on an alternative investment for the balance not recovered from that investment. However, when an inconsistency occurs, the possibility of occurrence of multiple roots, it goes to the Modified Internal Rate of Return (MIRR) to provide a definition for decision making. The work suggests that this method can always be used TIRM, in a universal way, in making financial business decisions, because conceptually used (and calculated) values ​​of rates much closer to those operating in the market and in the knowledge of who makes the decision. In addition, this method is effective in check for investment projects with different planning horizons. DOI: http://dx.doi.org/10.5377/nexo.v26i2.1287 Nexo Revista Científica Vol. 26, No. 02, pp. 83-87/Diciembre 2013